2021
DOI: 10.1007/s11042-021-10882-4
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy attacks recognition based on 1D octal pattern, wavelet transform and EEG signals

Abstract: Electroencephalogram (EEG) signals have been generally utilized for diagnostic systems. Nowadays artificial intelligence-based systems have been proposed to classify EEG signals to ease diagnosis process. However, machine learning models have generally been used deep learning based classification model to reach high classification accuracies. This work focuses classification epilepsy attacks using EEG signals with a lightweight and simple classification model. Hence, an automated EEG classification model is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…For 3-class classification of EEG signals, CNN classifiers can provide accuracies of 94.46% [22] and 97.07% [23], which are much better than 91.70% accuracy obtained with multiscale entropy based SVM [6]. For 5-class classification, the accuracy for using CNN have been reported to be 95.84% in the research work [23], which is also comparable to the classification accuracy of 96% obtained with octal pattern and wavelet transform based KNN [25].…”
Section: Introductionmentioning
confidence: 57%
“…For 3-class classification of EEG signals, CNN classifiers can provide accuracies of 94.46% [22] and 97.07% [23], which are much better than 91.70% accuracy obtained with multiscale entropy based SVM [6]. For 5-class classification, the accuracy for using CNN have been reported to be 95.84% in the research work [23], which is also comparable to the classification accuracy of 96% obtained with octal pattern and wavelet transform based KNN [25].…”
Section: Introductionmentioning
confidence: 57%
“…The results are arranged in ascending order of publication year. It is observed from [19], Akyol [20], Ayesha and coauthors [23], Sujatha [22], and Tuncer and coauthors [24], it is observed that the proposed study achieves better performance than the existing ones. Our outcomes reflect that the proposed approach has potentials to act as a significant tool to assist clinicians for detecting epilepsy.…”
Section: Methods Prime Attributesmentioning
confidence: 87%
“…For inter-ictal and ictal EEG signals classification, the highest accuracy of 99.38% was reported using the fuzzy rough nearest neighbor (FRNN). A new feature generation method based on 1D octal pattern for the classification of epileptic seizure is proposed by Tuncer and coauthors in [24]. For selecting EEG features, neighborhood component analysis was used and KNN did the classification.…”
Section: Related Workmentioning
confidence: 99%
“…They use the extracted eigenvalues to classify EEG signals and detect epilepsy. Tuncer T et al [6] proposed a lightweight and simple classification model to automatically detect seizures, and achieved effective results. The accuracy of classification reached 96.0%.…”
Section: Introductionmentioning
confidence: 99%